DEVELOPING ATTACK POINT IN VOLLEYBALL GAME USING PLYOMETRIC EXERCISES AT 13-14 YEARS OLD VOLLEYBALL PLAYERS - Ioan Sabin SOPA (Editura Universitatii Transilvania din Brasov, 2019)
The research started from the need to develop physical strength and speed and also to improve the jumping abilities of a women volleyball team. The research had as experiment group a team of 15 girls with age between 13-14 years old (13 ± 1.20 years old) and a volleyball experience between 5 and 6 years old (5 ± 1.50 years of experience). The experiment started in January 2018 and ended in October 2018 with five stages: documenting, initial testing, plyometric training, and final testing and statistical analyze. Research methods included five physical tests: standing long jump, triple broad jump, standing vertical jump, spiking point, and block point. The experiment group followed a four months plyometric program for improving jumping abilities and the results were analyzed statistically for significance. The conclusions of our research showed that the plyometric program included in the experiment had good results in both five tests but statistically significant results were found in standing long jump test, triple broad jump test and in block point.